2020
DOI: 10.1111/radm.12424
|View full text |Cite
|
Sign up to set email alerts
|

R &D investments and profitability during the crisis: evidence from Greece

Abstract: Innovation and Research and Development (R&D) investments have been considered in the literature as a significant determinant of corporate development and sustainability. Previous studies have examined the impact of intangibles on financial performance but not extensively within economic environments of intense financial turmoil. The scope of this study is to shed further light on this issue and examine whether R&D investments had an impact on the profitability of Greek firms especially during the sovereign de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Firms with high fixed assets efficiency (for firms of the chemicals and plastics industries), labour efficiency (pharmaceutical firms), gross profit margin (pharmaceuticals and chemicals firms) and with small size (chemicals and plastics firms) have been proven to be more profitable during the period of 2008-2011(Voulgaris and Lemonakis, 2014. For the tourism sector, the determinants of firm profitability that have been reported are the age of the firm, the size, the market share, the low high market share, the capitalisation, the investments, the turnover and the low leverage and cost-efficiency (Magoutas et al, 2016;Agiomirgianakis et al, 2013;Dimitri c et al, 2019;Dimitropoulos, 2020).…”
Section: The Firm Profitability In the Case Of Greecementioning
confidence: 99%
“…Firms with high fixed assets efficiency (for firms of the chemicals and plastics industries), labour efficiency (pharmaceutical firms), gross profit margin (pharmaceuticals and chemicals firms) and with small size (chemicals and plastics firms) have been proven to be more profitable during the period of 2008-2011(Voulgaris and Lemonakis, 2014. For the tourism sector, the determinants of firm profitability that have been reported are the age of the firm, the size, the market share, the low high market share, the capitalisation, the investments, the turnover and the low leverage and cost-efficiency (Magoutas et al, 2016;Agiomirgianakis et al, 2013;Dimitri c et al, 2019;Dimitropoulos, 2020).…”
Section: The Firm Profitability In the Case Of Greecementioning
confidence: 99%
“…According to this model, growth cannot go on forever without innovation as diminishing returns would reduce investment (Morales, 2003). At the micro-level, companies invest in R&D to create new products (Lee and Wu, 2015;Pindado et al, 2015), to achieve continuous innovation (Lee and Wu, 2015) and thus increase profits (Lee and Wu, 2015;Dimitropoulos, 2020) and corporate value (Poletti Hughes, 2008). At the macro-level, R&D expenditures may accelerate technological change and innovation (Pindado et al, 2015) and increase academic research productivity (Teitel, 1994) and thus foster growth (Boeing et al, 2022).…”
Section: Economics and Financementioning
confidence: 99%
“…At the micro-level, companies invest in R&D to create new products (Lee and Wu, 2015; Pindado et al. , 2015), to achieve continuous innovation (Lee and Wu, 2015) and thus increase profits (Lee and Wu, 2015; Dimitropoulos, 2020) and corporate value (Poletti Hughes, 2008). At the macro-level, R&D expenditures may accelerate technological change and innovation (Pindado et al.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The experience from previous studies showed that during the time of crisis, the firm focused on the R&D activity and marketing strategy (Knudsen & Lien, 2019;Dimitropoulos, 2020). The unique feature of the fintech company is innovation, which strongly links to R&D activity (Dorfleitner, Hornuf, Schmitt, and Weber, 2017;Arner, Arner, Barberis, and Buckley, 2015).…”
Section: Consolidation Strategymentioning
confidence: 99%